2009
DOI: 10.1002/cbic.200900512
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Counterion Activators for DNA: Stimuli‐Responsive Cation Transporters and Biosensors in Bulk and Lipid Bilayer Membranes

Abstract: We report that amphiphilic counterions can enable DNA to act as cation carrier, enzyme detector and biosensor. Calf thymus DNA is used as example throughout the study. Evaluation of a series of counterion activators suggests that strong amphiphilicity, alkyl or calix[4]arene tails and guanidinium cations give best results, whereas weak amphiphilicity, bola-amphiphilicity, planar aryl tails and ammonium cations are less satisfactory for various reasons. In the U-tube, DNA-counterion complexes can carry cations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 83 publications
0
64
0
Order By: Relevance
“…However, previous controls in the U-tube have confirmed that counterion-activated DNA can act as cation carrier at low concentrations. [20] In a typical procedure, octopus amphiphile G1H4O8 was added as concentrated stock solution in DMSO to the stirred and thermostated suspension of fluorogenic vesicles (Figure 2). Unchanged fluorescence at this point confirmed that octopus amphiphiles G1H4O8 alone are not active in lipid bilayer membranes.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous controls in the U-tube have confirmed that counterion-activated DNA can act as cation carrier at low concentrations. [20] In a typical procedure, octopus amphiphile G1H4O8 was added as concentrated stock solution in DMSO to the stirred and thermostated suspension of fluorogenic vesicles (Figure 2). Unchanged fluorescence at this point confirmed that octopus amphiphiles G1H4O8 alone are not active in lipid bilayer membranes.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…[2][3][4] The synthesis of transport systems [5][6][7][8][9][10][11][12][13][14][15][16][17] that respond to chemical stimulation was the first key step to achieve this goal. [18][19][20] In sensing systems, these stimuli-responsive transporters function as signal transducers. Their combination with enzymes as signal generators [21,22] afforded the first functional sensors that are operational in complex matrices from the supermarket to hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…S4A †; previous U-tube analysis has shown that countercation-activated ctDNA transports the cationic DPX but not the anionic HPTS across bulk liquid membranes). 31 Before the addition of DNA polyions, cationic amphiphiles A1H1O1-G1H3O30 did not cause a fluorescence response and were thus membrane-inactive under the selected, optimized conditions (Figs. S4A, S6A, S7A, S8A †).…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31] This problem has been solved with the in situ introduction of hydrophilic headgroups that can react with hydrophobic analytes to afford amphiphilic counterions which, in turn, can activate polyion transporters and generate a ''turnon'' fluorescent response (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…To ensure biological compatibility of our liposome assay we employed osmotic balanced (isotonic) vesicles suspensions in Tris buffered media (pH = 7.4). This routine assay report on internal dyes release as an increase in the HPTS fluorescence (Figure B) . The typical transport experiment consisted in measuring the HPTS fluorescence kinetics of a suspension of liposomes (EYPC‐LUVs⊃HPTS/DPX) in Tris buffer (pH = 7.4) upon addition (at t = 25 s) of amphiphile [ (OxTy) m Arg n , in which y denotes the number of aldehyde carbon atoms], followed by the anionic biopolymer (i.e., Herr‐DNA at t = 50 s) and finally, excess of Triton‐X (at t = 250 s) ( Figure A and Supporting Information).…”
Section: General Set Of Anionic Polymers Object Of This Studymentioning
confidence: 99%